Description of the unknown stages of Simulium (Aspathia) sandyi Coscaron, Ibanez-Bernal & Coscaron-Arias (Diptera: Simuliidae) - Sandoval-Ruiz, César A.; Ibáñez-Bernal, Sergio (Zootaxa, 2006)
The pharate male and the larva of Simulium (Aspathia) sandyi Coscarón, Ibáñez-Bernal & Coscarón-Arias, 1999, are described for the first time, and the female and pupa are redescribed. The most important features of the larva, pupa, male, and female are illustrated, and the previously reported type locality is corrected.